INCIDENCE RATE OF SUBCLINICAL MASTITIS IN ETAWA GOATS AT RAKA ETAWA FARM, SINGAPADU KALER VILLAGE, KECAMATAN SUKAWATI, GIANYAR DISTRICT, BALI - Vincetius Paulo Jinotra; Nyoman Adi Suratma; I Wayan Masa Tenaya; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Subclinical mastitis is an inflammatory condition of the mammary glands that occurs in livestock, including goats, without visually obvious or noticeable symptoms in the milk or mammary glands. Despite not showing typical symptoms such as discoloration, texture, or swelling of the milk, subclinical mastitis can have a negative impact on milk production and overall health of the herd. This study aimed to determine the incidence rate of mastitis in PE goats at Raka Etawa Farm, Singapadu Kaler Village, Sukawati District, Gianyar Regency, Bali. This type of research is observational, with the research design used is a cross sectional study by collecting data on the incidence rate of mastitis through the California Mastitis Test (CMT) in PE goats at Raka Etawa Farm at a certain point in time without involving intervention or supervision over a longer period of time. There were 15 lactating goats that were sampled for CMT test. Examination of subclinical mastitis in 15 PE goat milk samples resulted in 13 goats (87%) positive and 2 goats (13%) negative with details of 4 goats positive 2 (++) and 9 goats positive 3 (+++). Based on this study, it was concluded that PE goats in Raka Etawa Farm, Singapadu Kaler Village, Sukawati District, Gianyar Regency, Bali have a high incidence of subclinical mastitis. It is recommended to conduct routine CMT tests so that veterinarians can immediately provide appropriate treatment. This will contribute to the health and welfare of livestock, as well as assist farm owners in maintaining milk productivity and the sustainability of their farm business.